Penjadwalan Produksi Paving Block Pada CV. Nibo Corporation Banda Aceh - Heri Tri Irawan; Iing Pamungkas; Arhami Arhami (Jurnal Optimalisasi, 2020)
This paper uses the Palmer method to schedule paving block production in CV. Nibo Corporation Banda Aceh. CV. Nibo Corporation is engaged in the production of paving blocks located in the city of Banda Aceh. Problems faced by CV. Nibo Corporation often produces excess paving blocks than the number of orders that results in product accumulation in the storage area. The purpose of this study is to schedule paving block production in CV. Nibo Corporation. Paving block production scheduling in CV. Nibo Corporation will use the Palmer method. This research begins by calculating each standard time for each job. From the scheduling results, the comparison between the initial factory work schedule is nine hours of work in one day, and twenty-four working days in a month. While scheduling using the palmer method is six hours of work in one day and twenty-four working days in a month, or nine hours of work in one work day and seventeen days in a month. Using the palmer method can reduce the difference in production and orders every month from 31.000 to 5.944, or 3.000 per month, thereby reducing the accumulation of paving block products.